Children's co-construction of gender segregated spaces. (5th October 2022) - Bateman, Amanda
Abstract : This article aims to add to a growing body of work that applies an ethnomethodological framework to the study of children's play and games, and also to the exploration of the use of gender categories in social organization practices. Video recordings of four-year-old children's everyday play at an early childhood centre in New Zealand and primary school playground in mid-Wales, UK are analysed through detailed transcriptions using membership categorization analysis. The analysis reveals children's explicit reference to gender categories as a resource for social organization practices, offering insight into the systematic ways in which children co-construct the inclusion and exclusion of their peers. Access to play spaces is mediated on gender bias, where reference to gender categories is made interactionally relevant and procedurally consequential by children in their play. As such, this article demonstrates how children collaboratively make rules that exclude and include peers from play spaces through making gender categories demonstrably interactionally relevant in their everyday play.